P29 An audit of HIV partner notification practices in the North East. (23rd May 2012) - Dolan, G; Foster, K; Kain, K
Abstract : Background: Late diagnosis of HIV not only carries a risk of poorer outcomes for the individual, but of ongoing transmission of infection. Effective partner notification (PN) is key to identifying sexual contacts that may have been exposed, providing the opportunity to offer necessary advice, support and testing. Aim: This audit explored current PN practices across the North East in order to identify opportunities for improvement and inform future guidance. Methods: All genitourinary medicine and infectious diseases clinics across the North East were asked to complete questionnaires for up to ten newly diagnosed cases of HIV between January and December 2010, and provide additional background information on PN arrangements. Data were analysed used EpiData version 3.1. Results: Seven out of nine (78%) clinics responded. PN was discussed with 82% (46/56) of newly diagnosed patients and documented in the records of 77% (43/56). The time taken to complete all PN outcomes ranged from 0–29 weeks (median 1.5 weeks) and a mixture of methods were used to calculate the PN period. A total of 70 regular partners were recorded, 32 of which were tested and 44% (14/32) found to be HIV positive. 95 casual partners were recorded, nine of which were tested and none found to the HIV positive. Additional outcomes such as safe sex discussions and condom use were generally less frequently documented. Discussion and Conclusion: Although this sample is relatively small, there was engagement from the majority of regional services, suggesting that it is likely to be representative of local practice. It is clear that there is variation in current PN practices between clinics, and there are a number of challenges which may be particularly pertinent to HIV infection. These findings will be used to inform local policy and standards with the aim of improving the quality of local services and ensuring accountability for actions.